Istorijos mokslo ir audiovizualinės istorijos santykis Lietuvoje: nuotolio mažėjimas? - Šermukšnytė, Rūta (Lietuvos istorijos studijos, 2006)
The article is aimed at enumerating the barriers to cooperation between audio-visual communications specialists and formal historians in Lithuania in the 1988-2005 period, determining preconditions for overcoming these stumbling blocks and demonstrating the gap between these two spheres plus the consequences of its narrowing for audio-visual work. Documentary films and documentary-type cultural programs in which recognizable historical reports are discernible and which were made in the 1988-2005 period were used to achieve these aims. Stumbling blocks for historians preventing cooperation with audio-visual communications specialists are held to be the following: an arrogant position on the part of academics in regard to mass media, the inappropriate application of scientific standards in judging films and programs due to a lack of understanding of the individual specific features of the cinema and television, and the failure of historians to popularize their research. Stumbling blocks on the part of audio-visual communications specialists arise from the artistic / individual / creative documentary tradition in Lithuania which developed during the Soviet period. This tradition gave rise to attempts to transform history to conform more to the author’s vision of the past than to provide information based on the latest advances of formal, academic history. By trying to consider history emotionally and subjectively, the authors of Lithuanian documentary films and programs in the period of national revival and the first years of independence (till 1993) usually failed to provide a new, individual take on the history of Lithuania; rather, they reproduced interpretations of Lithuanian history produced in the 19th and early 20th centuries. The enhanced role of historians in the creation of Lithuanian documentary film and television is connected with changes in self-conception among audio-visual communications specialists (authors and their "supervising" critics) as well as among historians; these changes were visible by 1993. Out of this cooperation between audio-visual communications specialists and historians, there appeared works in Lithuanian audio-visual culture in which, because of the specific nature of cinematic and television methods, "neuralgic" themes in terms of historical consciousness were actualized (popularized), single-sided assessments of the past were rejected, and a history "open" to multiple viewpoints and to corrections in the future was created, thus demonstrating the problematic nature of history and more closely approaching the status of a scientific reconstruction.